2015
DOI: 10.1121/1.4922516
|View full text |Cite
|
Sign up to set email alerts
|

Improving the efficiency of deconvolution algorithms for sound source localization

Abstract: The localization of sound sources with delay-and-sum (DAS) beamforming is limited by a poor spatial resolution-particularly at low frequencies. Various methods based on deconvolution are examined to improve the resolution of the beamforming map, which can be modeled by a convolution of the unknown acoustic source distribution and the beamformer's response to a point source, i.e., point-spread function. A significant limitation of deconvolution is, however, an additional computational effort compared to beamfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…The computational grid of DAMAS needs to be fine enough, and too thick grid points will also cause spatial mixing of sound source distribution. In addition, DAMAS has the disadvantages of large computation and long operation time 16 . Some studies have shown that DAMAS with low frequency resolution has some advantages for the larger aperture array 17 .…”
Section: Deconvolution Algorithmsmentioning
confidence: 99%
“…The computational grid of DAMAS needs to be fine enough, and too thick grid points will also cause spatial mixing of sound source distribution. In addition, DAMAS has the disadvantages of large computation and long operation time 16 . Some studies have shown that DAMAS with low frequency resolution has some advantages for the larger aperture array 17 .…”
Section: Deconvolution Algorithmsmentioning
confidence: 99%
“…After conversion to the PSF shift‐invariant model, fast algorithms based on the fast Fourier transform (FFT) can be used to solve the problem (e.g. DAMAS2 [14], FISTA–DAMAS [22], FFT–NNLS [23], FFT–RL [24]). Unfortunately, in the underwater environment, it is difficult to establish a suitable mapping relationship to convert a PSF shift‐variant model into a PSF shift‐invariant model.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, research on sound detection technology for the design of microphone arrays and sound source localization algorithms [15][16][17][18][19] has been conducted.…”
Section: Introductionmentioning
confidence: 99%